Fluid Mechanics of Pressurized Circulating Fluidized Beds - Wirth, Karl-Ernst (Preprints 7th Internat. Conference on Fluidization, 1992)
A fluid mechanical model of segregated vertical gas-solids flow has been developed. Mass and force balances were set up with the aid of this model and, finally, a dimensionless state and pressure drop diagram was calculated. In this diagram, the pressure gradient causedby the solids transport is plotted in dimensionless form versus the superficial gas velocity in the form of a par- ticle Froude number. Parameter is the ratio of the solids volumetric flow rate at minimum fluidization tothe gas volumetric flow rate. The state and pressure drop diagram is valid for a given gas-solids system, i.e. for a given Archimed es number and given inimum fluidizationporosity. The fluid mechanical behaviour of different types of circulating fluidized beds can be  explained with the aid of the state and pressure drop diagram for segregated vertical gas-solids flow. As an example, the operating behaviourof circulating fluidized bed with a syphon in the solids downcomer is discussed. Measurements of the circulating solids mass flow rates arecom- pared with calculation results
UnivIS-Import:2015-04-16:Pub.1992.tech.ITC.mechve.fluidm_73
Keywords: fluidization